Tinjauan Yuridis Penyelesaian Sengketa Konsumen Akibat Penjualan Pupuk Bersubsidi Palsu - Unayah Pujawati; Grasia Kurniati (Universitas Batanghari Jambi, 2021)
The limited availability of subsidized fertilizers sold at official kiosk outlets makes it difficult for some farmers to get them. Not a few farmers who decide to buy subsidized fertilizer in other places whose authenticity is not guaranteed. As a result there are some farmers who are deceived by sellers of fake subsidized fertilizers. Therefore, a legal provision was made to protect the rights of farmers as consumers, and to deter sellers of fake subsidized fertilizers from taking action. Business actors must also be responsible for the consequences of losses suffered by consumers. This study aims to determine the factors causing the sale of counterfeit fertilizers and how the mechanism for resolving consumer disputes due to the sale of counterfeit fertilizers is based on Law Number 8 of 1999 concerning Consumer Protection. the research method used is normative juridical. The results of the study found that the factors that caused the sale of fake subsidized fertilizers were the lack of caution of consumers in purchasing subsidized fertilizers, the absence of responsibility for business actors, and the ease of obtaining raw materials for making fake fertilizers. Settlement of consumer disputes as legal protection for farmers can be reached through three stages, namely conciliation, mediation, and arbitration.